Classification of Surface EMG Using Wavelet Packet Energy Analysis and a Genetic Algorithm-Based Support Vector Machine - Rong, Y.; Hao, D.; Han, X.; Zhang, Y.; Zhang, J.; Zeng, Y. (Нейрофизиология, 2013)
The aim of our study was to recognize results of surface electromyography (sEMG) recorded under conditions of a maximum voluntary contraction (MVС) and fatigue states using wavelet packet transform and energy analysis. The sEMG signals were recorded in 10 young men from the right upper limb with a handgrip. sEMG signals were decomposed by wavelet packet transform, and the corresponding energies of certain frequencies were normalized as feature vectors. A back-propagation neural network, a support vector machine (SVM), and a genetic algorithm-based SVM (GA-SVM) worked as classifiers to distinguish muscle states. The results showed that muscle fatigue and MVC could be identified by level-4 wavelet packet transform and GA-SVM more accurately than when using other approaches. The classification correct rate reached 97.3% with sevenfold cross-validation. The proposed method can be used to adequately reflect the muscle activity. Ціллю нашого дослідження була розробка прийомів розпізнавання результатів електроміографічних відведень за допомогою поверхневих електродів (пЕМГ) в умовах розвитку максимального довільного скорочення та станів втоми; використовували пакетне вейвлет-перетворення та аналіз енергії. Сигнали пЕМГ піддавалися декомпозиції із застосуванням пакетного вейвлет-перетворення, і відповідні оцінки енергії певних частот нормувались як вектор ознак. Нейронна мережа із зворотним проведенням, машина опорних векторів (SVM) та SVM, базована на генетичному алгоритмі (GA-SVM), працювали як класифікатори, що розпізнавали стани м’язів. Отримані результати показали, що стани м’язової втоми та максимального довільного скорочення можуть бути ідентифіковані за допомогою пакетного вейвлет-перетворення 4-го рівня точніше, ніж у разі застосування інших підходів. Рівень коректності класифікації при семиразовій кросвалідизації сягав 97.3 %. Запропонований метод може бути використаний для адекватного відображення м’язової активності.